2020
DOI: 10.3390/su13010126
|View full text |Cite
|
Sign up to set email alerts
|

Ti/RuO2-IrO2-SnO2 Anode for Electrochemical Degradation of Pollutants in Pharmaceutical Wastewater: Optimization and Degradation Performances

Abstract: Electrochemical oxidation technology is an effective technique to treat high-concentration wastewater, which can directly oxidize refractory pollutants into simple inorganic compounds such as H2O and CO2. In this work, two-dimensionally stable anodes, Ti/RuO2-IrO2-SnO2, have been developed in order to degrade organic pollutants from pharmaceutical wastewater. Characterization by scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD) showed that the oxide coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 40 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…While, COD is the total sum of all chemically oxidizable forms in the solution, TOC is the sum of only the organic carbon (C-H) remaining in the solution. The difference is in line with other works cited in literature (Zhang et al 2021;Patidar et al 2022).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…While, COD is the total sum of all chemically oxidizable forms in the solution, TOC is the sum of only the organic carbon (C-H) remaining in the solution. The difference is in line with other works cited in literature (Zhang et al 2021;Patidar et al 2022).…”
Section: Resultssupporting
confidence: 92%
“…In electrochemical oxidation, surface area of electrode was found to be a crucial factor as it was directly proportional to the amount of hydroxyl radical production and direct electron transfer at the anode(Sharma et al 2020; Boudreau et al 2018;Zhang et al 2021). Figure2(a) shows the effect of electrode surface area on COD removal at 112 mg/L of DEP concentration, 22 mA/cm 2 current density and pH 3 in 60 min treatment time.…”
mentioning
confidence: 99%
“…( 22) is usually used to evaluate the energy consumption during electrochemical oxidation processes. It is expressed per g of removed COD (48).…”
Section: Specific Energy Consumptionmentioning
confidence: 99%
“…Ruthenium dioxide coated titanium (Ti‐RuO 2 ) anode is an emerging alternative over other anodes for the EO of organic pollutants. It has been reported to be dimensionally stable and noncorrosive and exposed high electrocatalytic action in order to produce varieties of robust oxidants (Cl − , •OH, H 2 O 2 , O 3 ) (Carneiro et al, 2005; Chauhan & Srivastava, 2022; Kaur et al, 2018, 2019a,b; Kim et al, 2003; Kumar et al, 2015; Wang, 2021; Zhang et al, 2019, 2021). Further, to the best of the authors' knowledge, no study on EO of 4‐ABP aromatic amine have been reported.…”
Section: Introductionmentioning
confidence: 99%